Concept of Business Dispute Resolution from a Justice Perspective - Herikson P. Siahaan; Triono Eddy; Ramlan Ramlan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Business activities are broader than trade, because the scope of business activities is not only trade, but covers broader fields such as production, processing, distribution, trade/marketing, export-import, procurement of goods/services, labor recruitment services, business consulting services , credit, credit guarantees, insurance, business cooperation, investment, mass media, property, capital markets, and others. The concept of resolution is that a private judge is not bound by various formalities, is quick in giving decisions, because it is in the final instance and is binding, which is easy to implement because the parties will obey it. Juridically based on Article 1 point 1 of Law no. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution (UUAAPS) arbitration is a method of resolving a civil dispute outside the general court which is based on an arbitration agreement made in writing by the parties to the dispute. The Supreme Court of the Republic of Indonesia said that ADR is a concept of cooperative resolution of conflicts or disputes outside of court which is directed at an agreement or solution to a conflict or dispute that is "win-win". What is meant by a "win-win" solution is a solution or agreement that is able to reflect the interests or needs of all parties involved in the conflict (shared interest).